2017
DOI: 10.1590/1807-1929/agriambi.v21n1p14-20
|View full text |Cite
|
Sign up to set email alerts
|

Cultivation of CNPA G3 sesame irrigated with saline water and fertilized with nitrate-N and ammonium-N

Abstract: A B S T R A C TThe study aimed to evaluate the effects of irrigation with saline water and fertilization with nitrate (NO 3 --N) and ammonium (NH 4 + -N) ratios on growth, flowering, water consumption and water use efficiency of the sesame cv. CNPA G3. The treatments were distributed in randomized blocks in a 5 x 5 factorial with three replicates, referring to five levels of electrical conductivity of the irrigation water -ECw (0.6, 1.2, 1.8, 2.4 and 3.0 dS m

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2018
2018
2019
2019

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 14 publications
1
1
0
Order By: Relevance
“…For the number of days to flower bud opening as a function of organic matter doses in the soil (Figure 5), with increasing OM doses, NDFBO decreased, with a maximum value (51 days) at an OM dose of 0%; however, the lowest value (42 days) was obtained at the OM dose of 3.3%. The early crop cycle observed in the present study can therefore be considered as an important characteristic, since the Brazilian programs of genetic improvement seek to select increasingly precocious cotton genotypes, aiming at maximum yields within shorter cultivation periods (LIMA et al, 2017). Likewise, Araújo et al (2001), evaluating the application of increasing doses of organic matter in the form of pig manure in the snap bean crop, also found an advance in the flowering stage, resulting in earlier harvest.…”
Section: Figuresupporting
confidence: 61%
“…For the number of days to flower bud opening as a function of organic matter doses in the soil (Figure 5), with increasing OM doses, NDFBO decreased, with a maximum value (51 days) at an OM dose of 0%; however, the lowest value (42 days) was obtained at the OM dose of 3.3%. The early crop cycle observed in the present study can therefore be considered as an important characteristic, since the Brazilian programs of genetic improvement seek to select increasingly precocious cotton genotypes, aiming at maximum yields within shorter cultivation periods (LIMA et al, 2017). Likewise, Araújo et al (2001), evaluating the application of increasing doses of organic matter in the form of pig manure in the snap bean crop, also found an advance in the flowering stage, resulting in earlier harvest.…”
Section: Figuresupporting
confidence: 61%
“…According to the regression equation for the stem diameter of the cotton plant ( Figure 1(b)), it can be observed that the plants showed reductions of 31.85 and 28.85%, respectively, at 80 and 100 DAS, in the plants submitted to the highest ECw in comparison with the lowest level of water salinity (1.5 dS•m −1 ). Therefore, due to the reductions in stem diameter, as well as in height, they show a reflection of excess salts in the root zone, causing a deleterious effect on the growth of the plants, which showed a marked decrease in the growth of different organs, because the excess of salts restricts the turgor of expanding tissues [22]. Following the same trend as plant height and stem diameter (Figure 1 the leaf area and number of leaves were negatively influenced by the increase of ECw (Figure 2), in the evaluations performed at 80 and 100 DAS.…”
Section: Resultsmentioning
confidence: 99%